DYNAMICS OF ECONOMIC GROWTH IN AGRICULTURE SECTOR AND FARMER’S TERM OF TRADE IN INDONESIA - Eddy Junaidi; Miftakhul Jannah (MESP–FEB UNS, 2020)
The agricultural sector is a sector that supports the economy in Indonesia has been proven to be able to survive the Indonesian crisis in 1997-1998 and during the COVID-19 pandemic crisis. This is evidenced by the large contribution of the Agricultural, Forestry, and Fisheries Industry to the national economy. Improving farmers' welfare needs to be prioritized after seeing the agricultural sector which continues to grow positively during the COVID-19 pandemic. However, in the second quarter of 2020 there was a decline in the exchange rate of farmers. Thus, a study is needed to analyze the exchange rate of farmers from year to year which can describe the movement of farmer welfare from 2011-2020. The results show the pattern of Economic Growth in the agricultural sector and Farmer’s Term of Trade s fluctuate, where if we look more deeply it shows a leading pattern for Economic Growth against FTT which shows that Agriculture Growth can It is used to predict Farmer’s Term of Trade, meanwhile Farmer’s Term of Trade cannot predict Agriculture Growth. Besides, it is observed that each sub-sector is proven to have their respective characteristics with a fluctuating pattern where the relationships formed generally have a unidirectional relationship wherein the Food Crops, Horticulture Crops and Animal Husbandry subsectors the relationships formed indicate that Economic Growth can be used to predict FTT. Meanwhile, in the Estate Crops and Fishery subsector, the relationship that is formed shows that FTT can be used to predict Economic Growth.Keywords: Agriculture, Economic growth, Farmer’s term of trade, Subsectors